DESAIN PENGEMBANGAN KURIKULUM - Humaedah Huma (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2021)
Curriculum development design is the arrangement or design of a curriculum model designed in accordance with the vision and mission of the school which in its development goes through a process of validation, implementation and evaluation. The steps that need to be considered when designing curriculum development are identifying the mission of educational institutions and the needs of education users, assessing the needs of learners, setting educational goals, selecting educational strategies, implementing the new curriculum, evaluating and providing feedback to improve the curriculum.The type of research methodology used is a research library with a philosophical approach which functions to conduct content analysis through conceptual and linguistic analysis. Linguistic analysis is used to help find the real meaning behind the facts, while concept analysis is used as a helper to find the meaning of words that are considered the main or key that has ideas.